2003
DOI: 10.1086/376731
|View full text |Cite
|
Sign up to set email alerts
|

Iron Abundance in the Intracluster Medium at High Redshift

Abstract: We present the analysis of the X-ray spectra of 18 distant clusters of galaxies with redshift 0:3 < z < 1:3. Most of them were observed with the Chandra satellite in long exposures ranging from 36 to 180 ks. For two of the z > 1 clusters, we also use deep XMM-Newton observations. Overall, these clusters probe the temperature range 3 keVdkTd8 keV. Our analysis is aimed at deriving the iron abundance in the intracluster medium (ICM) out to the highest redshifts probed to date. Using a combined spectral fit of cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
141
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(180 citation statements)
references
References 60 publications
39
141
0
Order By: Relevance
“…If metals produced and stored in LBG halos by z = 2.3 end up in clusters, than the average metallicity of the intracluster medium is Z I C M = Ω sf h Z /Ω I C M = 0.31Z , having assumed (Fukugita, Hogan & Peebles 1998) Ω I C M = 0.0026h −1.5 70 . Not only is this number tantalizingly close to the observed value at z = 1.2 (Tozzi et al 2003), but we also predict that little evolution will be found in the ICM metallicity up to z ≈ 2 as essentially all the metals that could have escaped galaxies during cosmic evolution had already done so by this epoch.…”
Section: Discussionsupporting
confidence: 81%
“…If metals produced and stored in LBG halos by z = 2.3 end up in clusters, than the average metallicity of the intracluster medium is Z I C M = Ω sf h Z /Ω I C M = 0.31Z , having assumed (Fukugita, Hogan & Peebles 1998) Ω I C M = 0.0026h −1.5 70 . Not only is this number tantalizingly close to the observed value at z = 1.2 (Tozzi et al 2003), but we also predict that little evolution will be found in the ICM metallicity up to z ≈ 2 as essentially all the metals that could have escaped galaxies during cosmic evolution had already done so by this epoch.…”
Section: Discussionsupporting
confidence: 81%
“…We note here that the values of L bol and T of RDCS 1252 are consistent with the local L À T relation measured by Markevitch (1998), and, when combined with all the other data available on distant clusters in the Chandra archive, suggest only a mild positive evolution of the L X -T relation (see discussion in Ettori et al 2003a and references therein). Our best-fit value of the metallicity, Z ¼ 0:36 þ0:12 À0:10 Z , lends further support to a lack of evolution of the ICM mean metallicity measured out to z ' 1.3 (see the analysis by Tozzi et al 2003, which did not include RDCS 1252).…”
Section: Discussionsupporting
confidence: 59%
“…In more distant and complex systems, such as putative protoclusters dominated by a powerful radio galaxy, Chandra deep pointings have only revealed nonthermal components in the diffuse plasma so far (Fabian et al 2003a;Scharf et al 2003). XMM-Newton observations of very distant clusters, although affected by source confusion in some circumstances, have the ability to collect a large number of photons, thus improving temperature determinations and allowing an estimate of the ICM metallicity (Hashimoto et al 2002;Tozzi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We performed a spectral temperature fit in a signal-to-noise optimized aperture of 40 following the procedure described in Tozzi et al (2003). Applying the same general procedure as for XMM-Newton with the local background measured in an onchip region with 60 diameter, we obtain a best fitting Chandra core temperature of 5.40 +1.27 −0.94 keV with the abundance fixed at 0.3 Z .…”
Section: Chandramentioning
confidence: 99%